AKTIVISME TAGAR #PERCUMALAPORPOLISI SEBAGAI ZEITGEIST DEMOKRASI SIBER DI INDONESIA - Wuriani, Nur Indah (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The uses of hashtag (#) in social media especially Twitter are no longer segmented for building popular conversation related to entertainment topics or trendings. Twitter users actively use hashtags to involve themselves in some political issues, in order to amplify some collective movements or merely to share their opinions and attitudes on specific issues. The concept is known as hashtag activism. Hashtag activism as a part of cyber democracy could only happen in two conditions, when the internet has widely penetrated the society and the uses of social media are becoming more common in the society. This research proposes that hashtag activism is scientifically satisfied four formal properties of cyber democracy's zeitgeist which are duration, scope, course also media and carrier, especially in Indonesia. Through netnography method and the usage Talkwalker, an automatic hashtag analyzer, the research focuses on analyzing the elements of formal properties of Zeitgeist in hashtag #PercumaLaporPolisi on Twitter.